Cell Disruption and Pressurized Liquid Extraction of Carotenoids from Microalgae - Taucher, Josephine; Baer, Sascha; Schwerna, Philipp; Hofmann, Dominik; Hümmer, Magdalena; Buchholz, Rainer; Becker, Anna (Journal of Thermodynamics & Catalysis, 2016)
Microalgae are very promising organisms for the production of high-value compounds such as carotenoids. Nevertheless, their commercial use is so far hampered by the lack of efficient processes and currently feasible for very few strains. One of the most relevant factors is the high effort for downstream processing, e.g., cell disruption and extraction. Thus, the presented studies were dedicated to investigate and optimize these two steps for carotenoid production with microalgae. Six different cell disruption techniques (high pressure homogenizer, ball mill, Ultra Turrax, repeated freeze and thaw, freeze-drying, ultra-sonication) were compared in lab scale for three species: Haemotococcus pluvialis, Chromochloris zofingiensis and Chlorella sorokiniana. The carotenoid recovery was determined via HPLC-UV/Vis after pressurized solvent extraction. Furthermore, factors influencing the applied extraction methods such as solvent, temperature, duration and number of cycles were optimized in order to reach highest recovery rates. While rough mechanical methods such as ball mill and high pressure homogenizer showed the highest effectivity for cell disruption of all three investigated strains, the influence of non-mechanical methods - i.e., repeated freeze and thaw cycles - on the efficiency of the extraction of astaxanthin, lutein and β-carotene increased reversely proportional to cell size and cell wall rigidity. For H. pluvialis repeated freezing and thawing resulted in a factor 240 times lower extraction yield compared to high pressure homogenizer, while both methods were comparable for C. sorokiniana. From six tested solvents, dichloromethane resulted in the highest carotene recovery yield, three times higher in comparison to n-hexane. Variation of the extraction temperature from room temperature to 120°C showed an optimum at 60°C. Nearly complete extraction was reached after one cycle of 10 minutes. The data presented here demonstrate the necessity of lab scale optimization of cell disruption and extraction process for future upscaling.
Keywords: H. pluvialis; C. sorokiniana; C. zofingiensis; Carotenoids; Cell disruption; Pressurized liquid extraction; HPLC